أبعاد تطبيق جودة خدمة الرعاية التمريضية: دراسة تطبيقية على مستشفى كسلا التعليمي - أ. د. علي عبدالله الحاكم; عبد الغفار عبدالله حامد على (White Nile Journal for Studies and Research, 2013)
This study aimed to identify the dimensions of the application of service quality of nursing care in a hospital in Kassala Teaching in Sudan, after a review of the literature search was building the model and assumptions depending on the theory of social exchanges, is designed questionnaire for data collection was developed standards depending on previous studies, depending on the random sample was distribute ۱۰۰ questionnaire recall which AA response rate of M%, used several statistical methods, including Cronbach's alpha and factor analysis to ensure reliability and stability, and to identify the relationship dimensions of application quality of service of nursing care level of service quality of nursing care in the hospital in general was used analysis of variance of the regression ANOVA, which which revealed no relationship between them in general, and in part results of the analysis of a relationship between the dimensions of the application of empathy and the level of service quality of nursing care in the hospital in general, and on the results of the study was to provide a number of recommendations related to the dimensions of the application of service quality of nursing care to upgrade the overall quality the service of nursing care. have also been proposals for future studies